REGULATION ANALYSIS IN THE PROTECTION OF CULTURAL HERITAGE IN MEDAN CITY (STUDY OF MEDAN CITY CULTURAL SERVICE) - Ridho Zikrillah; Ismed Batubara (SEAN Institute, 2022)
An urban area needs to pay attention to historical heritage as an effort to utilize resources in the spatial dimension to achieve a better urban area. Historic buildings are one sourcae of income to increase foreign exchange through foreign tourist visits. Preservation of historic buildings in areas in Medan City is a very appropriate step to be implemented. Preservation of buildings has the aim of saving the preservation of objects that still survive today. From several cases we find a fact that often historical buildings are decreasing and being replaced with more modern buildings. For this reason, it is necessary to immediately preserve and protect it. Based on this, the author is interested in researching it and it is stated in the title